Simultaneous adsorption of ammonia and phosphate using ferric sulfate modified carbon/zeolite composite from coal gasification slag. (1st March 2022) - Ma, Xianyao; Li, Yingxue; Xu, Defu; Tian, Hanxin; Yang, Hong
Abstract: Removal of nutrients in water is crucial to control eutrophication. Fly ash has been increasingly used to synthesize zeolite to remove nutrients, but it is still poorly understood about the removal capacity of zeolite synthesized from coal gasification slag (CGS), which has not been well recycled in many countries. In this study, the CGS was acid leached, alkali dissolved, and synthesized to carbon/zeolite composite (C/ZC) under induction by medical stone. After being modified by ferric sulfate, the composite was analyzed for the adsorption of NH4 + and PO4 3− . Results showed that the maximum adsorption capacity by C/ZC is 5.17 mg/g, but C/ZC has no adsorption capacity of PO4 3− . The ferric sulfate was used to modify C/ZC to obtain carbon/zeolite composite modified by iron (M-C/ZC). M-C/ZC has a higher specific surface area (348.3 m 2 /g), and the negatively charge of M-C/ZC can adsorb NH4 + and form Fe–O–P between PO4 3− and Fe–OH bonds. The maximum adsorption capacity of NH4 + and PO4 3− by M-C/ZC are 7.44 mg/g and 6.94 mg/g, respectively. The removal efficiency of NH4 + and PO4 3− are up to 88% and 99% under initial NH4 + (5 mg/L) and PO4 3− (10 mg/L) concentration. The regeneration capacity of M-C/ZC of NH4 + was stronger than that of PO4 3− . After three cycles, the regeneration rate of M-C/ZC of NH4 + was still up to 76.96%. Our findings suggest the good application potential of M-C/ZC for removing NH4 + and PO4 3− from wastewater. Graphical abstract: Image 1 Highlights: Coal gasification slag was used to synthesize carbon/zeolite composite. Carbon/zeolite composite can adsorb NH4 −, but not PO4 3- . Iron modification improved the adsorption capacity of carbon/zeolite composite. The maximum adsorption capacity for NH4 − and PO4 3− are 7.44 mg/g and 6.94 mg/g.